Numerical analysis of circular and square concrete filled aluminum tubes under axial compression - Pan Jinlong (Frattura ed Integrità Strutturale, 2020)
In this paper, the finite element (FE) method was used to investigate the axial compressive behaviors of circular and square concrete filled aluminum tubes (CFAT). Firstly, the simulation results were compared with the experimental results and the accuracy of the proposed FE model was verified. On this basis, the FE model was further applied to compare the mechanical properties of both circular and square CFATs under axial compression. It was found that the circular CFATs have a better effect on restraining the core concrete than square CFATs. The parametric analysis was also conducted based on the proposed FE model. It was noticed that the mechanical differences of the two kinds of CFATs gradually decreased with the increase of the aluminum ratio, aluminum strength and concrete strength.